The Role of Tobacco Control Change Agents in Slowing the Spread of E-cigarettes in Thailand: An Analysis based on Diffusion of Innovations Theory - Chayutrakorn, Chalita; Jangkham, Sarunyar; Tubpond, Ekkapol; Pipattanachat, Vasin (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study examines the mechanism of e-cigarette diffusion among Thai youth under the Diffusion of Innovations (DOI) framework. The objectives are to analyze factors based on DOI theory affecting the epidemic, synthesize the roles and strategies of tobacco control workers (Change Agents) in slowing the spread, and analyze related policy gaps. This is qualitative documentary research utilizing content analysis and policy analysis of policy documents, research, situation reports, and campaign media published between 2018–2024 (B.E. 2561–2567). The findings indicate that e-cigarettes possess all attributes under the DOI framework, which include relative advantage, compatibility, low complexity, trialability, and observability, which facilitate rapid adoption among youth. Change Agents, including teachers, Village Health Volunteers (VHVs), public health officers, community leaders, and local administrative organizations, play a crucial role in slowing diffusion. Their strategies include reducing the perceived advantage of e-cigarettes, reducing compatibility by creating positive identities for non-smokers, and increasing the perception of long-term harms and risks. However, operations face significant policy gaps: the gap between total ban policies and enforcement in online markets, the gap in the capacity of Change Agents, and the strategic communication gap that aligns poorly with youth media culture. The discussion suggests that DOI theory effectively explains the diffusion of negative innovations, leading to the proposal of a “counter-diffusion strategy” to develop modern preventive measures. Recommendations include developing mechanisms to regulate online markets, enhancing the digital competencies of Change Agents, adjusting communication strategies to be participatory and youth-led, and integrating e-cigarette control policies with national digital policies.